In Vitro Digestibility and Rumen Fermentation Parameters of Feeds as Affected by Supplementary Amla Powder and Fenugreek Seeds - Kumar, Dinesh; Singh, Putan; Chaturvedi, V. B.; Verma, A. K. (Indian Journal of Animal Nutrition, 2018)
The present study was designed to ascertain the effect of amla(Phyllanthus emblica L.) fruit powder (AFP) and fenugreek (Trigonella foenum-graecum L.) seeds (FS) supplementation on ruminal feed degradability,methane and microbial biomass production (MBP) under in vitro conditions. Concentrate mixture and wheat straw in 60: 40 ratio (on DM basis) was taken as substrate for the experiment. AFP, FS or AFP + FS mixture (1:1 ratio) was added at 1, 2 and 3% of the substrate, respectively. Digestibility of DM and OM improved (P